Characterisation of a rapidly solidified Al-V-Fe alloy - Humphreys, E; Warren, P; Cerezo, A (1998)
This paper outlines preliminary results from a combined XRD: TEM and APFIM investigation of a rapidly solidified Al94V4Fe2 alloy that had been produced by melt spinning. The microstructure produced consists of a high volume fraction (approximate to 50%) of 20 nm icosahedral particles in an f.c.c. matrix. Three-dimensional atom probe analysis shows that this second phase is enriched in iron and vanadium compared with the matrix. The thermal stability of the melt-spun ribbon has been investigated using DSC. It was found to be stable up to a temperature of 520 degrees C, after which there were two solid state transformations. (C) 1998 Elsevier Science S.A. All rights reserved.